Improving the detection and control of Fusarium oxysporum f. sp. elaeidis - Adusei-Fosu, KWASI (2017)
Fusarium wilt of oil palm, caused by a soil-borne fungal pathogen Fusarium oxysporum f. sp. elaeidis (Foe), is a major problem to oil palm cultivation and palm oil yield in Africa, Asia, and parts of North America. There is currently a shortfall in palm oil to meet local and international demands. Thus, factors constraining maximum yield are critical to address. This research was done to find potential methods of controlling Foe in Ghana and if possible extended to other countries experiencing similar problems. Effective disease control will come from understanding the genetic variability of Foe, a combination of selection and release of resistant germplasm, and rapid detection of Foe. In-depth molecular fingerprinting via AFLP, SSR, ISSR as well as using the “housekeeping” genes (TEF and ITS) and effector proteins specifically SIX genes as molecular markers revealed genetic variations among different isolates of Foe from Africa (Ghana, Ivory Coast, DR Congo) and South America (Suriname) as shown in the various constructed phylogenetic trees in the study. This research has introduced improved measures to obtain resistant oil palm germplasm from the high local genetic diversity via pathogenicity studies. Pathogenicity assessment under green-house conditions through different inoculation techniques revealed four Foe isolates could cause infection in oil palm genotypes from Ghana and Malaysia. Effectors based on fourteen SIX genes were studied and primers with higher specificity designed for the LAMP technique for only Foe detection or diagnosis on site developed. Different LAMP primer sets were developed in this study to distinguish or discriminate only Fusarium oxysporum isolates from other pathogens. A P-450 cytochrome gene LAMP primer was also successfully developed in this research. Survey of the disease was conducted in four different oil palm plantation fields in Ghana. Tissue samples were collected from symptomatic oil palm trees neighbouring asymptomatic oil palm trees in fields of Ghana as part of the survey. All tissue samples from both symptomatic and asymptomatic oil palm tested positive for Foe infection via PCR. General observations in the oil palm plantations in Ghana showed that infection of Foe occurred in clusters among oil palm trees. Application of different control mechanisms against Foe with biological agents (Trichoderma sp.), chemical (sodium silicate pentahydrate - Na2O3Si.5H2O) or photochemical (Conventional UV or High Intensity Pulsed Polychromatic source) techniques all proved to be potential methods to suppress or totally inhibit Foe. Among the three Trichoderma sp. used in the study, Trichoderma harzianum (T3) was the most suppressive to the four Foe isolates, though the other two Trichoderma isolates, T. cerinum (T1) and T. atroviride (T2) showed potential as biological control agents (BCAs). The three different concentrations of Na2O3Si.5H2O test yielded varying results as increasing concentrations increased the percentage inhibition in all four Foe isolates used. The lethal dose for Foe spores with either a High Intensity Pulsed Polychromatic or Conventional UV sources was 60 KJ but oil palm pollen exposed to this dose did not germinate. Generally, the higher the dose of UV, the lower the percentage germination of the oil palm pollen in this study.